Analisis Hidrologi Sub DAS Riam Kanan Pada Kejadian Banjir di Kabupaten Banjar - Novitasari Novitasari (Universitas Lambung Mangkurat, 2007)
Flood in Banjar’s Regency was caused by high frequency rainfall. Rainfall is the most important input component in the hydrologic process. This aim of this study is to give the hydrologic analysis at the Riam Kanan Sub catchment. Specific Model needed in study of stream characteristic with the approach to existing system complexity in a catchment, hence compatible model used is such as Even Model and Continuous Model. Based of both study, even in high flow analysis or low flow analysis there was a similar cause the flood at the Riam Kanan Sub catchment, landuse changed. The result of this study indicated that the hydrologic analysis of Banjar’s Regency flood been caused by effect of land use changed, by reduction of forest area become the area of settlement and opened mining.